Ménière's disease and allergy: Allergens and cytokines - Keleş, Erol; Gödekmerdan, Ahmet; Kalida?, Turgut; Kaygusuz, Irfan; Yalçin, Şinasi; Alpay, H. Cengiz; Aral, Murat (Royal Society of Medicine Press Ltd, 2004)
The aim of this article is to evaluate the role of allergy in the pathogenesis of Ménière's disease by means of cytokine profiles, allergic parameters and lymphocyte subgroups. A total of 46 patients aged between 26-68 years diagnosed with Ménière's disease between 1993-2002 were recruited to this study. The control group consisted of 46 healthy volunteers who were from the same age group, living in the same region and possessing similar socioeconomic indicators. Lymphocyte subgroups were measured from the peripheral blood by employing Becton Dickinson (BD) monoclonal CD4, CD8, CD23 antibodies. IFN-?, IL4, total IgE levels, and specific IgE levels pertaining to tree, fungus, fruit, egg-white, cow's milk, wheat flour, corn flour, beef, and rice allergens, in all seasons, were measured and compared in the patient and control groups. In patient serum samples there were positive correlations between CD23 and IgE, CD8 and IgE, CD4/CD8 and IgE, and CD23 and CD8 (p<0.01). There were negative correlations between IL-4 and IFN-?, IFN-? and IgE, and a positive correlation between IL-4 and IgE. Total IgE levels were above the normal values in 19/46 (41.3 per cent) of the patient group, but the ratio was nine out of 46 (19.5 per cent) in the control group. A history of allergy was found in 31/46 (67.3 per cent) when the patients were questioned. The ratio of a history of allergy was 16/46 (34.7 per cent) in the control group. When specific IgE levels were evaluated the ratio of patients with all the panels negative was eight out of 46 (17.9 per cent), but it was 31/46 (67.3 per cent) in the control group. This study found that the prevalence of allergy was higher in patients with Ménière's disease than in the control group. Thus the authors suggest that allergy should be taken into account when patients with this disease are treated.
Keywords: Cytokines; Hypersensitivity; Lymphocyte subsets; Ménière's disease